The double crisis of the welfare state and what we can do about it - Gooby, Peter Taylor- (Palgrave Macmillan, 2020)
Most people agree that the British welfare state faces problems. This book follows the guiding principle of much academic research: why let something be difficult when with careful reflection you can make it seem impossible? It also seeks to be positive.